Mechanical Ventilation - Lovich-Sapola, Jessica; Alter, Jonathan A.; Harders, Maureen (IntechOpen, 2022)
Mechanical ventilation, ventilator management, and weaning from mechanical ventilation vary based on location within the hospital, type of lung injury, and medical condition of the patient. Understanding the types of lung injury and various methods of achieving ventilation expand the armamentarium of the practitioner and allow for the best management decisions. This book begins with the use of a high-flow nasal cannula (HFNC) and a detailed description of the advanced modes of ventilation. The information on the types of ventilation can then be applied to the ventilation approaches in different populations of patients: the trauma patients, the obese patients, and the patients under neurocritical care. The conclusion contains a discussion of the mechanisms on how to wean from mechanical ventilation and how certain medical conditions affect the weaning process.